Managerial Positions Attainment and Gender Earnings Differential in Thailand’s Finance Sector - SrungBoonmee, Tanyamat (Human Resource and Organization Development Journal, 2021)
This paper uses data from the Thai Labor Force Survey (LFS) from 2012 – 2015 to study gender earnings differential among white collar workers in the Thai finance sector. The Blinder-Oaxaca (Blinder, 1973; Oaxaca, 1973) wage decomposition is employed in the investigation. The main results show a substantial unexplained earnings differential, but smaller than the explained difference. Family obligations do not seem to affect men and women differently. Further investigation reveals that the explained difference owes mostly to fewer females attaining management positions, as they tend to leave the profession at earlier ages than men. Insights from field interviews support the hypothesis that women are not as flexible in their work schedule as men are, while work in this sector often requires meeting clients at irregular hours. The inability or unwillingness of females to work those hours likely weakens their rapport with supervisors, which in turn hurt their chances of promotions.